2019
DOI: 10.1016/j.jweia.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of flow induced vibration of a flat plate located after a bluff wall mounted obstacle

Abstract: Accurate prediction of Flow Induced Vibration phenomena is currently a field of major interest due to the use of lightweight materials in the automotive and aerospace industry. This article studies the turbulent flow around a wallmounted obstacle, and the induced deformations produced by the pressure fluctuations on a plate located downstream the obstacle. The methodology used is a combination of experimental tests and numerical simulations. On one side, experiments were carried out in a wind tunnel test facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The main dimensions of the case of study can be found at Figure 2 The walls of the domain are supposed to be placed far enough from the plate in order to assume that the thin boundary layer is not signicantly aecting its aerodynamics. The distances have been chosen similar to those studied on the work of Torregrosa et al [23]. Here, they proposed the use of slip boundary conditions on channel walls in order to decrease the computational cost without jeopardizing the accuracy of the results and, therefore, a similar strategy is followed at the current work.…”
Section: Description Of the Test Casementioning
confidence: 99%
See 1 more Smart Citation
“…The main dimensions of the case of study can be found at Figure 2 The walls of the domain are supposed to be placed far enough from the plate in order to assume that the thin boundary layer is not signicantly aecting its aerodynamics. The distances have been chosen similar to those studied on the work of Torregrosa et al [23]. Here, they proposed the use of slip boundary conditions on channel walls in order to decrease the computational cost without jeopardizing the accuracy of the results and, therefore, a similar strategy is followed at the current work.…”
Section: Description Of the Test Casementioning
confidence: 99%
“…In rst place, the system can be completely dened without many diculties: (a) its mass and structural features are all well known; (b) the aerodynamic is complex and non-linearities can be identied for very low values of the angle of attack [22]. (c) Despite these complex aerodynamics, the detachment point is always located at the corner of the plate, leading to lift and moment coecients which are almost independent from the value of the Reynolds number as a rst approach [23]. Due to these features, and also to its direct applicability to other problems of the industry, the at plate has also been studied in similar works by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The recent developments can be reached out in refs. [14][15][16][17][18][19][20][21][22][23][24][25][26]. The accuracy of gas-liquid flow modeling is highly dependent on accurate interfacial force modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Torregrosa et al [25] investigated the turbulent flow and the pressure coefficient fluctuations downstream for a plate with surface-mounted obstacle. The surface-mounted obstacle generated great turbulent structures to excite unsteady flow and the pressure coefficient fluctuations downstream.…”
Section: Introductionmentioning
confidence: 99%